Coating materials to enhance the corrosion resistance of magnesium-based implants: a review - Slamet Saefudin; Purnomo Purnomo; Muhammad Omar Rusydi; Samsudi Raharjo; Kuzmin Anton; M. Edi Pujianto (SINERGI, 2026)
Biodegradable magnesium implants have attracted significant attention in orthopedics due to their low density, biocompatibility, and natural degradability in the human body. However, their clinical application has been limited by an excessively rapid degradation rate, which may compromise mechanical stability and disrupt tissue healing. To address this challenge, surface coating has been explored as an effective strategy to control the degradation rate, improve corrosion resistance, and preserve the mechanical integrity of magnesium implants. This review analyzed and compared various coating materials and methods applied to magnesium-based implants, including polymers, ceramics, metals, and composites. Each material category was found to offer distinct advantages and limitations in terms of biocompatibility, corrosion protection, and mechanical reinforcement. Furthermore, the study highlighted that the choice of coating method-such as dip coating, physical vapor deposition, micro-arc oxidation, or electrodeposition-significantly affected the performance of the protective layer. A structured literature search and qualitative synthesis of recent studies published between 2020 and 2025 were conducted to assess coating performance, identify trends, and evaluate challenges in clinical translation. The findings indicated that composite and multilayer coatings provided the most promising balance of corrosion resistance, bioactivity, and mechanical strength, despite fabrication complexity. This review concluded that the development of multifunctional coatings and standardized testing protocols remains crucial for advancing the clinical application of magnesium-based biodegradable implants.